Foundations and practice of security : 9th International Symposium, FPS 2016, Québec City, QC, Canada, October 24-25, 2016, Revised selected papers /: 9th International Symposium, FPS 2016, Québec City, QC, Canada, October 24-25, 2016, Revised selected papers. (2017) - Unknown
No abstract available